Hydrated nucleus pulposus herniation in seven dogs. Issue 3 (March 2015) - Manunta, M.L.; Evangelisti, M.A.; Bergknut, N.; Grinwis, G.C.M.; Ballocco, I.; Meij, B.P.
Highlights Cervical hydrated nucleus pulposus extrusion (HNPE) is an atypical presentation of disc extrusion in the dog. Follow-up magnetic resonance imaging (MRI) in conservatively treated dogs revealed disappearance of the extruded material. Histological examination of extruded material confirmed that it was nucleus pulposus with evidence of early degeneration.